Case report: Rare intrapulmonary malignant mesothelioma complicated with myositis - Gong, Dandan; Yu, Jian; Jiang, Xiaodong (Frontiers in Oncology, 2022)
Malignant pleural mesothelioma is an uncommon and aggressive tumor. The incidence is even lower when the lung parenchyma are the primary site.Myositis is a common paraneoplastic syndrome but rarely presenting on malignant pleural mesothelioma. In the report, we aim to present a rare case of intrapulmonary malignant mesothelioma complicated with cancer-associated myositis. The patient presented limb muscle weakness as first symptom and was diagnosised as intrapulmonary malignant mesothelioma complicated with cancer-associated myositis, based on clinical, histological, immunohistochemical, and radiological findings. The case had a poor response with conventional hormone therapy.